Catalogue of Naidinae and Pristininae (Annelida: Oligochaeta: Naididae) with twenty species new for Montenegro - Šundić, Danijela; Radujković, Branko M.; Krpo-Ćetković, Jasmina (Zootaxa, 2011)
The Oligochaeta occurring in Montenegrin freshwaters were studied in order to contribute to a better knowledge of this group in the region. The oligochaetes from rivers, lakes, reservoirs, creeks, and springs, belonging to the Black Sea and the Adriatic Sea drainage basins, were investigated. Samples of sediments were taken from 54 sampling sites during three years of research (2005–2008). We confirmed the presence of formerly reported species and found 20 species new for the Montenegrin oligochaete fauna: Chaetogaster cristallinus, C. diaphanus, C. langi, C. setosus, Nais behningi, N. bretscheri, N. elinguis, N. simplex, N. stolci, Ophidonais serpentina, Paranais frici, P. litoralis, Piguetiella blanci, Pristina bilobata, P. jenkinae, P. longiseta, P. osborni, P. proboscidea, Slavina appendiculata, and Uncinais uncinata. Accordingly, the fauna of Naidinae and Pristininae in Montenegro now consists of 36 species.